Is it More Intrinsic or Extrinsic? The Motivation of Gayonese EFL Students to Learn English - Mahmud, Salami; Akmal, Saiful; Arias, Ariska (SCAD Independent, 2023)
Motivation is a crucial concept for being successful in learning. Highly motivated students will do their best in learning any subject. This quantitative study aimed to investigate the predominant type of motivation among Gayonese students and their level of motivation to study English at the Department of English Language Education, Universitas Islam Negeri Ar-Raniry Banda Aceh. The research samples were 33 students from batch 2014 to batch 2018 from the Department of English Language Education from Gayo highland Districts (Central Aceh, Gayo Lues, and Bener Meriah Districts). The random sampling technique was used to select participants with close-ended questionnaires as the data collection instrument. The results showed that the overall intrinsic motivation score was greater than the extrinsic one (4.21 ˃ 3.05). As a result, the implication of this study requires teachers to boost students’ extrinsic motivation to increase their academic achievement in studying English at the university.